PEMBINAAN PEMBUDIDAYA IKAN KOI DI KELURAHAN BALANG BARU KOTA MAKASSAR - Hasnidar, Hasnidar; Tamsil, Andi; Akram, Andi Muhammad (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2023)
Ornamental fish farming in Makassar City is growing rapidly, both as a main livelihood and as an alternative. Demand continues to increase and prices are high, causing many people to cultivate freshwater ornamental fish, both as breeders and enlargement activities. One species of ornamental fish that has high economic value is koi fish (Cyprinus carpio). Along with the higher demand and the hope that new varieties will be found, cultivators/breeders are trying to do crosses. However, low lineage records and the use of unselected parents lead to frequent inbreeding. To obtain high-quality fish seeds, good parental quality, skills in reproduction, spawning, hatching, larval rearing and harvesting are needed. The ornamental fish cultivating group in kelurahan Balang Baru, kecamatan Tamalate, Makassar City as partners, was held on November 21, 2021. The aims of the PKM are: 1) Increasing public knowledge and understanding through counseling about the biology and reproduction aspects of koi fish; (2) Training on procedures for selecting broodstock, selecting and preparing broodstock for the process of reproduction, mating, spawning, hatching, rearing larvae, harvesting and packing. The expected outputs from this activity are: cultivators who become partners who understand the reproductive biology aspects of koi fish and are skilled at carrying out brood selection procedures, selecting and preparing broodstock for reproduction, mating, spawning, hatching, and larval rearing processes